Towards a Fiscal Pact : The Political Economy of Decentralization in Bolivia - Frank, Jonas (World Bank, Washington, DC, 2013)
The decentralization game in Bolivia has been altered quite significantly with the presence of new bargainers at the departmental level. Two, opposing groups have emerged and which follow intricate strategies to enforce their claims. The highland departments are strongly aligned to the Movimiento al Socialismo (MAS) party and the charismatic leadership of the country's first indigenous leader Evo Morales. The Media Luna departments in the lowlands demand autonomy and seek a greater share of the national pool of hydrocarbon revenue. The paper discusses how a fiscal pact can be forged to bring agreement around the most pressing issues. It considers several bargaining packages which could be crafted and analyzes the extent to which decentralization principles need to be sacrificed in order to achieve agreement among competing actors. It is likely that these agreements may eliminate some inefficiency, but also create others. An important insight is that the fiscal pact should be renegotiated at certain pre-defined times, in order to provide flexibility and adjust to the constraints of actors to engage in inter-temporal commitments. Explicit exit options would enhance the possibilities for agreement.